2014
DOI: 10.1016/j.freeradbiomed.2014.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Redox proteomics analysis of HNE-modified proteins in Down syndrome brain: clues for understanding the development of Alzheimer disease

Abstract: Down syndrome (DS) is the most common genetic cause of intellectual disability, due to partial or complete triplication of chromosome 21. DS subjects are characterized by a number of abnormalities including premature aging and development of Alzheimer’s disease (AD) neuropathology after approximately 40 years of age. Several studies show that oxidative stress plays a crucial role in the development of neurodegeneration in DS population. Increased lipid peroxidation is one of the main events causing redox imbal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
110
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(119 citation statements)
references
References 68 publications
7
110
1
Order By: Relevance
“…Previous studies from our group demonstrate impairments of the proteasome system (17) and the reduction of autophagosome function in DS, before and after the development of AD, which suggests that accumulation of oxidized/misfolded protein is an early hallmark in DS brain (59). We showed that some members of the PQC are oxidatively modified in young DS cases before the development of AD and that oxidation of target proteins possibly leads to impaired activity of clearance systems (19). We hypothesize that reduced protein degradation contributes to the accumulation of polyubiquitinated proteins, which, in turn, may act to disturb other cellular functions.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Previous studies from our group demonstrate impairments of the proteasome system (17) and the reduction of autophagosome function in DS, before and after the development of AD, which suggests that accumulation of oxidized/misfolded protein is an early hallmark in DS brain (59). We showed that some members of the PQC are oxidatively modified in young DS cases before the development of AD and that oxidation of target proteins possibly leads to impaired activity of clearance systems (19). We hypothesize that reduced protein degradation contributes to the accumulation of polyubiquitinated proteins, which, in turn, may act to disturb other cellular functions.…”
Section: Discussionsupporting
confidence: 55%
“…The proteomic results for UCH-L1 indicated an increased polyubiquitinylation in DS and DS/AD compared with their respective controls and also when comparing DS/AD with DS. We previously reported that UCH-L1 was increasingly carbonylated and also HNE modified in DS and DS/AD (17,19) brains and in brains from AD cases (7). Data from the validation analysis on UCH-L1 confirmed the elevated poly-Ub K63 in DS and DS/AD compared with their age-matched controls (2-and 1.6-fold, Fig.…”
Section: Fig 3 Proteomic Profile Of Representative 2d Blots (A)supporting
confidence: 52%
See 1 more Smart Citation
“…In contrast, elongation factor 1α is far more oxidized in total aggregates (27–31%) than in Aβ‐ or tau‐IP aggregates (0–13%). Oxidized proteins are thought to be more vulnerable to aggregation and were found to be elevated in a C. elegans model of AD (Boyd‐Kimball et al ., 2006) and in hippocampi of AD and aging Down's patients (Butterfield et al ., 2014; Di Domenico et al ., 2014). However, this report is the first (to our knowledge) to identify and quantify proteins and modifications from specific affinity‐purified aggregates, and the first to show unequal distribution of oxidized proteins among aggregate types, which must reflect differing properties of those classes (see Discussion).…”
Section: Resultsmentioning
confidence: 99%
“…For example, using MALDI-TOF specific targets of 4-hydroxy-2-nonenal modifications were identified in Down syndrome cases, supporting similarities with Alzheimer disease. Western blotting after 2D electrophoresis was carried out with a mouse monoclonal anti-HNE antibody, proteins in the corresponding digested spots were identified by MALDI-TOF peptide mass fingerprinting, and the data were searched using the Mascot search engine [113]. A similar method was also successfully applied in the identification of complex I subunits modified by HNE in mitochondria from diabetic kidney.…”
Section: -[(Hept-1-enyl)-4-hexylpyridinium]lysine (Hhp-lysine) a Nomentioning
confidence: 99%